Development of remote diagnostic monitoring system for pumping equipment with open architecture - Alexey Savostin; Kayrat Koshekov; Amandyk Tuleshov; Galina Savostina; Abay Koshekov (Радіоелектронні і комп'ютерні системи)
The study aim was to develop a remote diagnostic monitoring system for pumping equipment with an open architecture to improve the reliability and efficiency of pump operation in various industrial sectors. The system is designed for the periodic collection and analysis of vibration and temperature signals, which allows for the prompt identification of potential equipment malfunctions and avoidance of emergency shutdowns during the production process. The aim of this study was to develop an effective open architecture for a diagnostic monitoring system for pumping equipment based on IoT technologies. The primary focus is on creating a system architecture that simplifies the installation and operation of equipment, ensures scalability and ease of integration with existing enterprise information systems, and reduces material implementation costs. To achieve this goal, the following objectives were addressed within the study: 1) selection of informative features from vibration signals that allow for the diagnosis of the most common faults in pumping equipment during periodic monitoring; 2) selection of hardware specifications that ensure the diagnostic monitoring system meets the stated requirements; and 3) development of a software and network architecture for the diagnostic monitoring system based on open hardware and software standards. The results of the experiments demonstrated that the developed system enables effective monitoring of the condition of pumping equipment and reduces the risk of emergency shutdowns, thereby optimizing operating costs. The incorporation of wireless technologies, open software products, and standards makes systems flexible and cost-effective, which is especially important for small and medium-sized industrial enterprises. Conclusion. The use of the proposed monitoring system improves the reliability of pumping equipment and maintenance management based on the current state data.